Tobacco Use Behaviors and Perceptions of Parental Smokers in the Emergency Department Setting. (June 2019) - Mahabee-Gittens, E Melinda; Merianos, Ashley L; Stone, Lara; Tabangin, Meredith E; Khoury, Jane C; Gordon, Judith S
Background: More information is needed about modifiable child tobacco smoke exposure (TSE) patterns in racially diverse parental smokers to tailor interventions designed to help parents quit smoking and reduce their child's TSE. Our objectives were to determine whether there were differences in smoking and TSE patterns based on parental race and child age and whether these patterns differed based on child age within black and white parental smokers. Secondary objectives were to assess the relationship between parental perceptions about the effects of smoking and the benefits of quitting on their child based on child age, race, and reported TSE patterns and to examine biochemically verified TSE levels by child age, race, and parent-reported TSE patterns. Methods: Participants (N = 415) were non-Hispanic black and non-Hispanic white parental smokers, mean age (standard deviation [SD]) = 31.2 (7.2) years, who visited the Pediatric Emergency Department (PED) or Urgent Care (UC) with their child, mean age (SD) = 4.7 (4.6) years. Parents reported sociodemographics, smoking, and child TSE patterns. We conducted chi-square tests, independent t-tests, and general linear regression models to answer our primary objectives and linear regression models to answer our secondary objectives. Results: Parents were 56.1% non-Hispanic black; 87.5% women; mean (SD) number of cigarettes smoked/day was 10.5(6.8). A higher proportion of parents with younger children <3 years old reported smoking bans compared with parents with older children ⩾3 to <18 years old (41.3% vs 19.7%, P < .0001). Subsequent analyses revealed this pattern for both black and white parents. A total of 212 (51%) of children had biochemical assessment of TSE; 89.6% had detectable TSE. Younger children had significantly higher cotinine levels than older children independent of their race ( P < .001). Conclusions: Children of parental smokers who visit the PED/UC were highly tobacco smoke exposed. Both black and white parental smokers with younger children were more likely to enforce smoking bans, but younger children had higher TSE levels than older children. Interventions that target this group of parental smokers with younger children may be more effective than interventions geared to all parental smokers.